REALITY AND FAITH - Arvydas Šliogeris (Problemos)
This article asks a traditional question of Western metaphysics: what the reality is all about? Yet the traditional, ontological direction of this question is changed and the reality is questioned in terms of what the autor of this article calls an ontotopical point of view. So the question is about where the mortal being meets the reality as absolute transcendence. Two imanently given orientatins towards this ontotopical reality are discovered: the intensiveness-plus which spurts from vast expanses of sensible things, and the intensiveness-minus emanating from the expanses of pure language. The corresponding instance of the first intensiveness is the first hand, immediate vision of the sensible thing; the corresponding instance of the second one is an immediate belief and absolute trust in pure word. That is why the two places of the reality are ultimately discovered - the alpha-reality and omega-reality, the senseless sensual thing ard the senseless transsensual word.